Temporal Analysis of Property Values Before and After the Revitalization of Depok City Square, 2015–2025 - Rachmawati, Areez; Malau, Albert Gamot (Journal Research of Social Science, Economics, and Management, 2026)
Public space revitalization aims to improve environmental quality and drive regional economic growth. Depok City Square, revitalized in 2020, has undergone significant physical and social changes. This research analyzes property value changes around the square from 2015 to 2025, identifies spatial patterns of value increases, and evaluates the influencing factors. This quantitative study used secondary data (NJOP and property portals) and primary data from field surveys at 120 points within 0–2 km of the square. Analysis employed multiple linear regression (five variables: revitalization dummy, distance to square, distance to main road, commercial intensity, observation year) and GIS-based spatial mapping. The results showed that average property value increases ranged from 48.4% to 87.9% depending on the distance zone, with the highest increase occurring within a radius of 0–500 meters from the square. The regression model yielded an R² of 0.782, with the revitalization dummy variable as the largest determinant (? = Rp1,924,300/m²). Spatial patterns revealed an uneven distribution of increases, with commercial corridors on the west and north sides benefiting more than residential areas on the east and south sides. The study concludes that town square revitalization had a positive and significant impact on property values, but also triggered commercial gentrification pressures that displaced local MSMEs. Therefore, future revitalization policies need to integrate social protection dimensions and land value capture mechanisms to ensure equitable distribution of benefits.